Effects of different additives on the bacterial community and fermentation mode of whole-plant paper mulberry silage - Wu, Changrong; Sun, Wentao; Huang, Yuan; Dai, Sheng; Peng, Chao; Zheng, Yulong; Chen, Chao; Hao, Jun (Frontiers in Microbiology, 2022)
The aim of this study was to investigate the effects of additives, namely, two lactic acid bacteria (LAB) species (Lacticaseibacillus rhamnosus and Lentilactobacillus buchneri) and four corn flour percentages (0%, 3%, 6%, and 9%), on the composition and function of the bacterial community in whole-plant paper mulberry silage. The different additive treatments promoted Lactiplantibacillus, Lentilactobacillus and Lacticaseibacillus growth, but the microbial species responsible for fermentation differed among the treatments. High species diversity and various gram-negative bacteria, such as Flavitalea sp., Pantoea agglomerans, Acinetobacter pittii, Turicibacter sanguinis and Ralstonia pickettii, were found in the uninoculated LAB treatments. A beneficial bacterium, Lactobacillus johnsonii, was discovered for the first time in whole-plant paper mulberry silage. LAB inoculation simplifies the microbial community structure, and beneficial lactobacillus as a key species aggregates in the inoculated treatment group. However, L. rhamnosus inoculation alone may have limited bacteriostatic activity against in whole-plant paper mulberry silage. Compared with silage lacking corn flour, amino sugar and nucleotide sugar metabolism, galactose metabolism, the phosphotransferase system and the pentose phosphate pathway metabolic activity were increased in corn flour-containing silage. Whole-plant paper mulberry can be used as a high-quality silage to provide high-quality feed resources for sustainable ruminant livestock production. Moreover, additive use is necessary for preparing paper mulberry silage.